If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3r * 4rx + x + 12 = 0 Reorder the terms for easier multiplication: -3 * 4r * rx + x + 12 = 0 Multiply -3 * 4 -12r * rx + x + 12 = 0 Multiply r * rx -12r2x + x + 12 = 0 Reorder the terms: 12 + -12r2x + x = 0 Solving 12 + -12r2x + x = 0 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12r2x + -12 + x = 0 + -12 Reorder the terms: 12 + -12 + -12r2x + x = 0 + -12 Combine like terms: 12 + -12 = 0 0 + -12r2x + x = 0 + -12 -12r2x + x = 0 + -12 Combine like terms: 0 + -12 = -12 -12r2x + x = -12 Add '-1x' to each side of the equation. -12r2x + x + -1x = -12 + -1x Combine like terms: x + -1x = 0 -12r2x + 0 = -12 + -1x -12r2x = -12 + -1x Divide each side by '-12x'. r2 = x-1 + 0.08333333333 Simplifying r2 = x-1 + 0.08333333333 Reorder the terms: r2 = 0.08333333333 + x-1 Reorder the terms: -0.08333333333 + r2 + -1x-1 = 0.08333333333 + x-1 + -0.08333333333 + -1x-1 Reorder the terms: -0.08333333333 + r2 + -1x-1 = 0.08333333333 + -0.08333333333 + x-1 + -1x-1 Combine like terms: 0.08333333333 + -0.08333333333 = 0.00000000000 -0.08333333333 + r2 + -1x-1 = 0.00000000000 + x-1 + -1x-1 -0.08333333333 + r2 + -1x-1 = x-1 + -1x-1 Combine like terms: x-1 + -1x-1 = 0 -0.08333333333 + r2 + -1x-1 = 0 The solution to this equation could not be determined.
| -5=C-10 | | 15n^2-30n=0 | | 9(t-3)+36t=6(t+2) | | 3-(x-4)=2x+5 | | 12s^3+22s^2-70s=0 | | [10-5(x-2)]=(x+1) | | 5+5w=2+11w | | 6x-3=15-48 | | 3/x=9/2 | | 7/8*h=1/5 | | 35u^2-39u-14=0 | | 10.1+5.3=w | | 1=y(8y-4) | | 1,34x-5,4=x-3,7 | | 2*2=5y | | X^2+18+20=0 | | 4x=y(4x-4) | | -(14-2s)-(6s+4)=14 | | 4x^3+14x^2+166x+140=0 | | 4xy-4y-4x=0 | | 5r^2-6r+1=0 | | (31-0.5y)+(31-0.5y+4)+y=66 | | y=70+14(7) | | 2*40+3x=128 | | 73=x+0.32x | | 6x+ay=24 | | 2x+9x-4x=14+7 | | 0.03/9 | | 3x+ay=15 | | -2t^2+15t-15=0 | | x*x-v*v= | | 5x^2+21x-24=0 |